Co-modification of Seren Taun Traditional Ceremony on Community Identity Formation - Prasetyo, Untung; Sarwoprasodjo, Sarwititi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
This study is focused on the correlation of commodification the Seren Taun traditional ceremony within the form a community identity of Kampung Budaya Sindangbarang. The objective of the study was to determine 1) to what extent is the correlation between commodification the Seren Taun traditional ceremony and its motive of to implement the Seren Taun traditional ceremony, and 2) to what extent is the correlation between motive of to implement the Seren Taun traditional ceremony and its behavior of to implement of the Seren Taun traditional ceremony within the form a community identity of Kampung Budaya Sindangbarang. The reaserch showed that commodification the Seren Taun traditional ceremony was related to the form a community identity of Kampung Budaya Sindangbarang. The lower was commodification the Seren Taun traditional ceremony, then the higher was the form a community identity of Kampung Budaya Sindangbarang.The reaserch explained that community of Kampung Budaya Sindangbarang is consistent to look the Seren Taun traditional ceremony as their facility to describe about thanks be to God, to construction a community solidarity, to keep a community institutional, and to keep Sunda traditional art.